Isolation, antibacterial screening, and identification of bioactive cave dwelling bacteria in Fiji - Pipite, Atanas; Lockhart, Peter J.; McLenachan, Patricia A.; Christi, Ketan; Kumar, Dinesh; Prasad, Surendra; Subramani, Ramesh (Frontiers in Microbiology, 2022)
Bacteria are well known producers of bioactive secondary metabolites, including some of the most effective antibiotics in use today. While the caves of Oceania are still largely under-explored, they form oligotrophic and extreme environments that are a promising source for identifying novel species of bacteria with biologically active compounds. By using selective media that mimicked a cave environment, and pretreatments that suppressed the growth of fast-growing bacteria, we have cultured genetically diverse bacteria from a limestone cave in Fiji. Fifty-five isolates purified from culture had Actinomycete-like morphologies and these were investigated for antibacterial activity. Initial screening using a cross streak test with pathogenic bacteria indicated that 34 of the isolates had antibacterial properties. Partial 16S rRNA gene sequences from these isolates were determined and compared with 16S rRNA gene sequences in EzBioCloud and SILVA data bases. The best matches for the isolates are bacteria with potential uses in the manufacture of antibiotics and pesticides, in bioremediation of toxic waste, in biomining, in producing bioplastics, and in plant growth promotion. Nineteen bacteria were confirmed as Actinomycetes. Thirteen were from the genus Streptomyces and six from genera considered to be rare Actinomycetes from Pseudonocardia, Kocuria, Micromonospora, Nonomuraea. Ten isolates were Firmicutes from the genera Bacillus, Lysinbacillus, Psychrobacillus and Fontibacillus. Two were Proteobacteria from the genera Mesorhizobium and Cupriavidus. Our findings identify a potentially rich source of microbes for applications in biotechnologies.